Method for synthesizing spinel type nano-micro material based on subcritical technology
The synthesis of spinel nano-micromaterials through subcritical technology solves the problems of long preparation time, difficult to control the reaction atmosphere and uneven product distribution in traditional methods, and achieves the regulation of material structure and the improvement of catalytic performance.
Patent Information
- Application Number
- CN202510032086.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The traditional spinel nanomicromaterial synthesis method has problems such as long preparation time, difficulty in controlling the reaction atmosphere, and uneven product morphology and size distribution.
The spinel nano-micromaterials are synthesized by subcritical technology. By adjusting the temperature during the reaction process and entering different reaction atmospheres, the reaction rate and the growth rate of nano-microstructure are controlled, thereby realizing the structure of spinel nano-micromaterials. Regulation.
The structural regulation of spinel nanomicromaterials has been achieved, the photocatalytic degradation efficiency and catalytic conversion rate of the catalyst are improved, and the yield is also significantly improved.
Smart Images

Figure CN119430304A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of multi-metal materials, and specifically relates to a method for synthesizing spinel nano-micro materials based on subcritical technology. Background Art
[0002] With the continuous progress of nanotechnology and the deepening of interdisciplinary research, nanometal materials have attracted much attention due to their relatively small size, large specific surface area, large surface energy and surface binding energy, etc. This type of material can significantly improve the catalytic performance, electrical properties, magnetic properties and biocompatibility of the material by finely controlling the composition, distribution and microstructure of different metal elements, thus playing a key role in many fields such as catalytic chemistry, energy conversion and storage, biomedicine and electronic information devices.
[0003] However, traditional methods for synthesizing spinel nanomaterials, such as the sol-gel method, co-precipitation method, and hydrothermal method, often have problems such as long preparation time, difficult to control the reaction atmosphere, and uneven product morphology and size distribution. For example, although the components of the sol-gel method are controllable and easy to dope, its raw materials are expensive and the reaction takes a long time; although the co-precipitation method produces a small and uniform product particle size, the material is easy to agglomerate and the atmosphere cannot be precisely controlled to obtain the required material with specific functions in one step; although the product prepared by the hydrothermal method has high purity and a narrow particle size distribution, the preparation time is too long and the reaction atmosphere cannot be precisely controlled.
[0004] Subcritical technology is a method that uses the special properties of fluids (usually water or organic solvents) (such as density, solubility and diffusivity) to promote chemical reactions and material synthesis at specific temperatures and pressures. The principle of this technology is mainly to pass the precursor solution and additives into a mixer for mixing, and then quickly heat up the reactor to allow the crystals to rapidly nucleate and precipitate nanoparticles. Compared with traditional methods, subcritical technology has the advantages of short reaction time, easy control of reaction atmosphere, mild treatment process, small product particle size and uniform size distribution, etc., providing a method with significant advantages for the construction of spinel nanomaterials. Summary of the invention
[0005] In order to overcome the shortcomings and deficiencies in the prior art, the purpose of the present invention is to provide a method for synthesizing spinel nanomaterials based on subcritical technology. By adjusting the temperature during the reaction and introducing different reaction atmospheres, the reaction rate and the growth rate of the nanostructure are controlled, thereby achieving structural regulation of the spinel nanomaterial.
[0006] The subcritical technology method for synthesizing spinel nanomaterials is characterized in that its preparation method comprises the following steps: 1) Dissolve a variety of metal salts in ultrapure water, perform ultrasonic homogenization and set aside, weigh an organic additive and dissolve it in ultrapure water, mix the solutions to obtain a mixed solution, and transfer it to a subcritical high-pressure reactor after ultrasonication; 2) dispersing the alkaline additive in ultrapure water to obtain an alkaline solution, and dropping the alkaline solution into the mixed solution obtained in step 1), stirring and mixing evenly, sealing the reactor, and introducing air or other gases to remove air and dissolved oxygen in the system; under magnetic stirring, accurately controlling the temperature and pressure in the subcritical high-pressure reactor by a heating and pressurizing device, and maintaining the temperature and pressure for 30 to 180 minutes, so as to form a subcritical fluid with a certain pressure in the subcritical high-pressure reactor; 3) After the reaction is completed, the solution prepared in step 2) is centrifuged, washed with ultrapure water and anhydrous ethanol to remove residual salt, and dried in an oven overnight to obtain a spinel nano-micro material.
[0007] Furthermore, the metal salt in step 1) is a nitrate or chloride of aluminum, cobalt, manganese, zinc, bismuth, indium or iron.
[0008] Furthermore, the organic additive in step 1) is citric acid, thioacetamide, cetyltrimethylammonium bromide or urea, and the molar ratio of the total metal atoms in the metal salt solution to the added amount of the organic additive is 1:0.8~5.
[0009] Furthermore, the alkaline additive in step 2) is sodium hydroxide, ammonia water, carbonate or bicarbonate, and the molar amount of the alkaline additive in the alkaline solution to the total metal atom in the metal salt solution is 2-8:1.
[0010] Furthermore, in the temperature control step described in step 2), the temperature is controlled at 160-180°C, and when the prepared spinel nanomaterial is a sulfide catalyst, nitrogen is used, and when the prepared spinel nanomaterial is an oxidation catalyst, oxygen is used.
[0011] The beneficial effects achieved by the present invention are: 1) The petal structure of the ZnIn2S4 catalyst prepared by the subcritical technology of the present invention is more open, the particle surface area is larger and uniform without agglomeration, and the efficiency of the photocatalytic degradation of SMX is improved by 17.5% compared with the ZnIn2S4 catalyst prepared by the hydrothermal method; the ZnCo2O4 catalyst prepared by the subcritical technology has a nanoparticle cluster structure, and the conversion rate of the ZnCo2O4 catalyst in the catalytic conversion of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid is improved by 9.8% and the yield is improved by 11.5% compared with the ZnCo2O4 catalyst prepared by the hydrothermal method.
[0012] 2) The present invention has found that in the process of preparing catalysts using subcritical technology, different atmospheres are suitable for different catalyst types. The growth environment of the nanostructure can be controlled by adjusting the atmosphere, and the particle morphology of the material can be adjusted. When preparing spinel-type sulfide catalysts, it is more appropriate to introduce nitrogen as the atmosphere, and when preparing spinel-type oxidation catalysts, it is more appropriate to introduce oxygen as the atmosphere. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 XRD and SEM images of CoAl2O4 prepared in Example 1; Figure 2 XRD and SEM images of CoAl2O4 prepared in Example 2; Figure 3 XRD and SEM images of CuCo2O4 prepared in Example 3; Figure 4 XRD, SEM and TEM images of ZnCo2O4 prepared in Example 4; Figure 5 XRD, SEM and TEM images of ZnIn2S4 prepared in Example 5; Figure 6 This is the SEM image of ZnCo2O4 prepared in Comparative Example 1; Figure 7 This is a SEM comparison of ZnIn2S4 prepared in Example 6 and Comparative Example 2; Figure 8 This is a diagram of the subcritical fluid reactor apparatus.
[0014] In the figure: 1. Gas storage tank; 2. Intermediate container; 3. Subcritical high-pressure reactor; 4. Manual pump. DETAILED DESCRIPTION
[0015] The present invention will be further described below in conjunction with specific embodiments and the accompanying drawings, but the protection scope of the present invention is not limited thereto.
[0016] The device used in the subcritical technology in the following embodiments is as follows: Figure 8 As shown, the gas storage tank 1 is connected to the intermediate container 2, the water storage end of the intermediate container 2 is connected to the manual pump 4, the gas storage end of the intermediate container 2 is connected to the subcritical high-pressure reactor 3, and the manual pump 4 pushes pressure to the intermediate container 2 to allow the gas to enter the subcritical high-pressure reactor 3.
[0017] Example 1 The CoAl2O4 catalyst was synthesized using a subcritical technology method, and the steps are as follows: Dissolve 0.291 g Co(NO3)2·6H2O and 0.750 g Al(NO3)3·9H2O in 20 mL ultrapure water, and mix them evenly with ultrasound. Then weigh 0.630 g citric acid and dissolve it in 20 mL ultrapure water. Mix the two solutions to obtain a citric acid chelated metal mixed solution. After ultrasound, transfer it to a subcritical high-pressure reactor. Then weigh 0.360 g NaOH and disperse it in another 40 mL ultrapure water to obtain an alkaline solution. The alkaline solution is slowly added dropwise to the above-mentioned citric acid chelated metal mixed solution, and stirred to mix evenly; the reactor is sealed, oxygen is introduced to remove the air in the system, and under magnetic stirring, the pressure in the subcritical high-pressure reactor is controlled to be 0.1 MPa by operating a manual pump, and the temperature in the subcritical high-pressure reactor is controlled to be 180°C by a control panel and a temperature measuring line. The reaction is maintained for 120 minutes and then centrifuged. The obtained solid is washed three times with ultrapure water and anhydrous ethanol respectively to remove residual salt, and then dried in an oven at 60°C under vacuum to obtain a CoAl2O4 catalyst.
[0018] The XRD pattern of the CoAl2O4 catalyst prepared in Example 1 shows that the method of the present invention successfully prepared the CoAl2O4 catalyst (such as Figure 1 (a) in the figure); the SEM image shows that the CoAl2O4 prepared by the method of the present invention has a spherical nanostructure (such as Figure 1 (b) in the figure.
[0019] Example 2 The CoAl2O4 catalyst was synthesized using a subcritical technology method, and the steps are as follows: Dissolve 0.291 g Co(NO3)2·6H2O and 0.750 g Al(NO3)3·9H2O in 20 mL ultrapure water, and mix them evenly with ultrasound. Then weigh 0.630 g citric acid and dissolve it in 20 mL ultrapure water. Mix the two solutions to obtain a citric acid chelated metal mixed solution. After ultrasound, transfer it to a subcritical high-pressure reactor. Then weigh 0.360 g NaOH and disperse it in another 40 mL ultrapure water to obtain an alkaline solution. The alkaline solution is slowly added dropwise to the above-mentioned citric acid chelated metal mixed solution, and stirred to mix evenly; the reactor is sealed, nitrogen is introduced to remove air and dissolved oxygen in the system, and under magnetic stirring, the pressure in the high-pressure reactor is controlled to be 0.1 Mpa by operating a manual pump, and the temperature in the supercritical high-pressure reactor is controlled to be 180°C by a control panel and a temperature measuring line. The reaction is maintained for 120 minutes and then centrifuged. The obtained solid is washed 3 times with ultrapure water and anhydrous ethanol respectively to remove residual salt, and vacuum dried in an oven at 60°C to obtain a CoAl2O4 catalyst.
[0020] The XRD pattern of the CoAl2O4 catalyst prepared in Example 2 shows that the method of the present invention successfully prepared the CoAl2O4 catalyst (such as Figure 2(a) in the figure); the SEM image shows that the CoAl2O4 particles prepared by the method of the present invention have an inhomogeneous structure, containing both flake structures and small particle structures (such as Figure 2 (b) in the figure.
[0021] SEM images of CoAl2O4 prepared in Example 1 and Example 2 (as shown in Figure 1 (b) and Figure 2 The comparison of (b) in the figure shows that when preparing spinel-type oxidation catalysts, the atmospheres introduced are different. The atmosphere introduced in Example 1 is oxygen, and the atmosphere introduced in Example 2 is nitrogen. To a certain extent, the particles prepared by introducing oxygen are more uniform than those prepared by introducing nitrogen. Because when the catalyst is a spinel-type oxide, if nitrogen is introduced, the nitrogen may cause interference and cause changes in the crystal phase structure of the catalyst. Oxygen is a strong oxidant, which can easily oxidize the desired substance. At the same time, the oxide can promote the uniform growth of particles in an oxygen-rich environment and avoid excessive agglomeration or irregular growth of particles. Therefore, if the desired substance is a spinel-type oxide, the catalyst particles prepared by introducing oxygen will be more uniform.
[0022] Example 3 The CuCo2O4 catalyst synthesized using the subcritical technology method is as follows: Dissolve 0.242 g Cu(NO3)2·3H2O and 0.582 g Co(NO3)2·6H2O in 20 mL ultrapure water, and mix them evenly with ultrasound. Then, weigh 0.630 g citric acid and dissolve it in 20 mL ultrapure water. Mix the two solutions to obtain a citric acid chelated metal mixed solution. After ultrasound, transfer it to a subcritical high-pressure reactor. Then, weigh 0.360 g NaOH and disperse it in another 40 mL ultrapure water to obtain an alkaline solution. The alkaline solution is slowly added dropwise to the above-mentioned citric acid chelated metal mixture, and stirred to mix evenly; the reactor is sealed, oxygen is introduced to remove the air in the system, and under magnetic stirring, the pressure in the high-pressure reactor is controlled to be 0.1 Mpa by operating a manual pump, and the temperature in the supercritical high-pressure reactor is controlled to be 180°C by a control panel and a temperature measuring line. The reaction is maintained for 120 minutes and then centrifuged. The obtained solid is washed three times with ultrapure water and anhydrous ethanol respectively to remove residual salt, and then dried in an oven at 60°C under vacuum to obtain the CuCo2O4 catalyst.
[0023] The XRD pattern of the CuCo2O4 catalyst prepared in Example 3 shows that the method of the present invention successfully prepared the CuCo2O4 catalyst (such as Figure 3 (a) in the figure); SEM images show that the CuCo2O4 prepared by the method of the present invention has a nanoparticle cluster structure (such as Figure 3 (b) in the figure.
[0024] Example 4 Synthesis of ZnCo2O4 catalyst using subcritical technology and application, the steps are as follows: Dissolve 0.298 g Zn(NO3)2·6H2O and 0.582 g Co(NO3)2·6H2O in 20 mL ultrapure water, and mix them evenly with ultrasound. Then weigh 0.630 g citric acid and dissolve it in 20 mL ultrapure water. Mix the two solutions to obtain a citric acid chelated metal mixed solution. After ultrasound, transfer it to a subcritical high-pressure reactor. Then weigh 0.360 g NaOH and disperse it in another 40 mL ultrapure water to obtain an alkaline solution. The alkaline solution is slowly added dropwise to the above-mentioned citric acid chelated metal mixed solution, and stirred to mix evenly; the reactor is sealed, oxygen is introduced to remove the air in the system, and under magnetic stirring, the pressure in the subcritical high-pressure reactor is controlled to be 0.1 Mpa by operating a manual pump, and the temperature in the subcritical high-pressure reactor is controlled to be 160°C by a control panel and a temperature measuring line. The reaction is maintained for 120 minutes and then centrifuged. The obtained solid is washed three times with ultrapure water and anhydrous ethanol respectively to remove residual salt, and then dried in a vacuum oven at 60°C to obtain a ZnCo2O4 catalyst.
[0025] The XRD pattern of the ZnCo2O4 catalyst prepared in Example 4 shows that the method of the present invention successfully prepared the ZnCo2O4 catalyst (such as Figure 4 (a) in the figure); SEM images (such as Figure 4 (b) shows that the ZnCo2O4 prepared by the method of the present invention has a nanoparticle cluster structure, and the TEM image shows that the nanoparticles are polyhedral structures (such as Figure 4 (c) in the figure.
[0026] The ZnCo2O4 sample prepared in Example 4 was used to catalyze the conversion of 5-hydroxymethylfurfural into 2,5-furandicarboxylic acid, and the specific process was as follows: 1) A microreactor device was used, the inner tank was 25 mL, and a heating jacket was used to heat and control the temperature. 50 mg of ZnCo2O4 material prepared in Example 3 was filled, 0.042 g of sodium bicarbonate was filled, and 5 mL of 50 mM 5-hydroxymethylfurfural solution was filled. The microreactor was sealed, magnetic stirring was continued at 600 rpm, oxygen was pressurized to 1.5 MPa, the reaction temperature was raised to 130°C, the heating rate was 2°C / min, and the timing was started after the temperature reached 130°C, and the sample with a reaction time of 8h was made.
[0027] 2) The reaction temperature was controlled at 130°C to carry out the 5-hydroxymethylfurfural oxidation experiment. After the 5-hydroxymethylfurfural oxidation reaction reached stability, the 5-hydroxymethylfurfural (HMF) conversion rate could reach 86.7%, and the 2,5-furandicarboxylic acid (FDCA) yield could reach up to 36.2%, as shown in Table 1.
[0028] Comparative Example 1: ZnCo2O4 was prepared by hydrothermal method, the steps are as follows: Dissolve 0.298 g Zn(NO3)2·6H2O and 0.582 g Co(NO3)2·6H2O in 20 mL ultrapure water, mix them evenly by ultrasonication, and then weigh 0.630 g citric acid and dissolve them in 20 mL ultrapure water. Mix the two solutions to obtain a citric acid chelated metal mixture. Transfer them to a reactor after ultrasonication. Then weigh 0.360 g NaOH and disperse them in another 40 mL ultrapure water to obtain an alkaline solution. Slowly drop the alkaline solution into the above citric acid chelated metal mixture, stir and mix evenly, and then transfer to a 50 mL stainless steel autoclave lined with polytetrafluoroethylene. Then seal the autoclave and heat it in an oven at 160°C for 16 h. After the autoclave is cooled naturally to room temperature, collect the prepared ZnCo2O4 and wash it with deionized water and anhydrous ethanol three times. The collected powder is dried in a vacuum oven at 60°C overnight to obtain the ZnCo2O4 catalyst.
[0029] The SEM image of the ZnCo2O4 catalyst prepared in Comparative Example 1 shows that the ZnCo2O4 prepared by the method described in Comparative Example 1 has a granular nanostructure, but the particle size is uneven and there is agglomeration. Figure 6 .
[0030] The ZnCo2O4 sample prepared in Comparative Example 1 was used to catalyze the conversion of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid, and the specific process was as follows: 1) A microreactor device with a 25 mL inner tank was used, and a heating jacket was used to heat and control the temperature. 50 mg of ZnCo2O4 material prepared in Comparative Example 1 was loaded, 0.042 g of sodium bicarbonate was loaded, and 5 mL of 50 mM 5-hydroxymethylfurfural solution was loaded. The microreactor was sealed, magnetic stirring was continued at 600 rpm, oxygen was pressurized to 1.5 MPa, the reaction temperature was raised to 130°C, the heating rate was 2°C / min, and the timing was started after the temperature reached 130°C, and the sample with a reaction time of 8h was made.
[0031] 2) The reaction temperature was controlled at 130°C, and a 5-hydroxymethylfurfural oxidation experiment was conducted. After the 5-hydroxymethylfurfural oxidation reaction reached stability, the 5-hydroxymethylfurfural conversion rate could reach 76.9%, and the 2,5-furandicarboxylic acid yield was as high as 24.7%, indicating that the ZnCo2O4 catalyst prepared by the inventive method can be used to catalyze the conversion of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid, and the conversion rate and yield are higher than those of the ZnCo2O4 catalyst prepared by the hydrothermal method, as shown in Table 1.
[0032] Table 1 Comparison of catalytic effects of ZnCo2O4 catalysts prepared by different methods
[0033] Example 5 The multi-metal nanostructured catalyst ZnIn2S4 was synthesized using a subcritical technology method, and the steps are as follows: 0.068 g ZnCl2 and 0.293 g InCl3·4H2O were dissolved in 20 mL ultrapure water, and ultrasonically homogenized for later use. Then 0.15 g thioacetamide was weighed and dissolved in 20 mL ultrapure water, and the two solutions were mixed to obtain a mixed solution. After ultrasonication, the mixture was transferred to a subcritical high-pressure reactor. Then 0.360 g NaOH was weighed and dispersed in another 40 mL ultrapure water to obtain an alkaline solution. The alkaline solution was slowly added dropwise to the above citric acid chelated metal mixed solution, and stirred and mixed evenly. The reactor was sealed, and nitrogen was introduced to remove air and dissolved oxygen in the system. Under magnetic stirring, the pressure in the subcritical high-pressure reactor was controlled to 0.1 Mpa by operating a manual pump, and the temperature in the subcritical high-pressure reactor was controlled to 160°C by a control panel and a temperature measuring line. The reaction was maintained for 120 min and then centrifuged. The obtained solid was washed with ultrapure water and anhydrous ethanol for 3 times to remove residual salt, and dried in an oven at 60°C under vacuum to obtain the ZnIn2S4 catalyst.
[0034] The XRD pattern of the ZnIn2S4 catalyst prepared in Example 5 shows that the method of the present invention successfully prepared the ZnIn2S4 catalyst (such as Figure 5 (a) in the figure); the SEM image shows that the ZnIn2S4 prepared by the method of the present invention has a hexagonal flower-like microsphere structure, with uniform particle size and no agglomeration between particles (such as Figure 5 (b) in the figure), the TEM image shows that the microspheres are self-assembled from nanosheets on the core (e.g. Figure 5 (c) in the figure.
[0035] The ZnIn2S4 sample prepared in Example 5 was used for photocatalytic degradation of sulfamethoxazole (SMX), and the specific process was as follows: The photocatalytic degradation experiment of SMX under room temperature visible light (λ>420 nm) irradiation was carried out in a quartz reactor. The light source was a 300W Xe lamp, and the cutoff filter was 420 nm. 10 mg of the ZnIn2S4 photocatalyst prepared by Example 5 was added to 50 mL of the reaction solution containing SMX (1.5 mg / L). The prepared reaction mixture was ultrasonicated for 1 min, and the initial pH value was adjusted within the deviation range of ± 0.2 with NaOH (0.5M) and H2SO4 (0.25 M). The quartz reactor was placed on a magnetic stirrer and stirred for 30 min to allow SMX and the photocatalyst to reach adsorption-desorption equilibrium, and then the reaction was carried out under light.
[0036] The experiment shows that when the reaction time is 60 min, the efficiency of ZnIn2S4 photocatalytic degradation of SMX can reach 61.2%, see Table 2.
[0037] Example 6 The multi-metal nanostructured catalyst ZnIn2S4 was synthesized using a subcritical technology method, and the steps are as follows: 0.068 g ZnCl2 and 0.293 g InCl3·4H2O were dissolved in 20 mL ultrapure water, and ultrasonically homogenized for later use. Then 0.15 g thioacetamide was weighed and dissolved in 20 mL ultrapure water, and the two solutions were mixed to obtain a mixed solution. After ultrasonication, the solution was transferred to a subcritical high-pressure reactor. Then 0.360 g NaOH was weighed and dispersed in another 40 mL ultrapure water to obtain an alkaline solution. The alkaline solution was slowly added dropwise to the above citric acid chelated metal mixed solution, and stirred and mixed evenly. The reactor was sealed, and oxygen was introduced to remove the air in the system. Under magnetic stirring, the pressure in the subcritical high-pressure reactor was controlled to 0.1 Mpa by operating a manual pump, and the temperature in the subcritical high-pressure reactor was controlled to 160°C by a control panel and a temperature measuring line. After the reaction was maintained for 120 min, the reaction was centrifuged, and the obtained solid was washed with ultrapure water and anhydrous ethanol for 3 times to remove residual salt, and dried in an oven at 60°C under vacuum to obtain the ZnIn2S4 catalyst.
[0038] Comparative Example 2: ZnIn2S4 was prepared by hydrothermal method, the steps are as follows: Dissolve 0.068 g ZnCl2 and 0.293 g InCl3·4H2O in 20 mL ultrapure water, mix them by ultrasonication, and then weigh 0.15 g thioacetamide and dissolve it in 20 mL ultrapure water. Mix the two solutions to obtain a mixed solution. Transfer it to a reactor after ultrasonication. Then weigh 0.360 g NaOH and disperse it in another 40 mL ultrapure water to obtain an alkaline solution. Slowly drop the alkaline solution into the above citric acid chelated metal mixed solution, stir and mix well, and then transfer it to a 50 mL stainless steel autoclave lined with polytetrafluoroethylene. Then seal the autoclave and heat it in an oven at 160 °C for 16 h. After the autoclave is cooled naturally to room temperature, collect the prepared ZnIn2S4 and wash it with deionized water and anhydrous ethanol three times. The collected powder is dried in a vacuum oven at 60 °C overnight to obtain the ZnIn2S4 catalyst.
[0039] The SEM image of Example 5 shows that the ZnIn2S4 prepared by the method of the present invention has a hexagonal flower-like microsphere structure, with uniform particle size and no agglomeration between particles (such as Figure 5 (b) in Example 6); SEM image of Example 6 (as shown in Figure 7 (a) shows that the ZnIn2S4 prepared by the method of the present invention has a hexagonal flower-like microsphere structure, but Figure 5Compared with (b), its petals are smaller and some particles are agglomerated; the SEM image of the ZnIn2S4 catalyst prepared in Comparative Example 2 shows that the ZnIn2S4 prepared by the method described in Comparative Example 2 has a hexagonal flower-like microsphere structure, but the petals are smaller and there is agglomeration between the particles (see Figure 7 (b) in the figure); SEM images of ZnIn2S4 prepared in Example 5 and Example 6 (as shown in Figure 5 (b) and Figure 7 The comparison of (a) in Figure 1 shows that when preparing spinel sulfide, the atmosphere introduced is different. The atmosphere introduced in Example 5 is nitrogen, and the atmosphere introduced in Example 6 is oxygen. The particles prepared by introducing nitrogen are more uniform to a certain extent than those prepared by introducing oxygen. Because when the catalyst is spinel sulfide, if oxygen is introduced, the sulfide is easily oxidized, and nitrogen is an inert gas, which can drive away the air and moisture in the device, provide a stable protective environment, and prevent the material from being oxidized or contaminated during the preparation process, thereby ensuring the high purity and performance of the nanomaterial. Therefore, if the desired substance is spinel sulfide, the catalyst particles prepared by introducing nitrogen will be more uniform.
[0040] The ZnIn2S4 sample prepared in Comparative Example 2 was used for photocatalytic degradation of sulfamethoxazole (SMX), and the specific process was as follows: The photocatalytic degradation experiment of SMX under room temperature visible light (λ>420 nm) irradiation was carried out in a quartz reactor. The light source was a 300W Xe lamp, and the cutoff filter was 420 nm. 10 mg of the ZnIn2S4 photocatalyst prepared by Comparative Example 2 was added to 50 mL of a reaction solution containing SMX (1.5 mg / L). The prepared reaction mixture was ultrasonicated for 1 min, and the initial pH value was adjusted to a deviation range of ± 0.2 with NaOH (0.5M) and H2SO4 (0.25 M). The quartz reactor was placed on a magnetic stirrer and stirred for 30 min to allow SMX and the photocatalyst to reach adsorption-desorption equilibrium, and then the reaction was carried out under light.
[0041] Experiments show that when the reaction time is 60 min, the ZnIn2S4 catalyst prepared by the inventive method can photocatalytically degrade SMX, and the efficiency of photocatalytic degradation of SMX is higher than that of the ZnIn2S4 catalyst prepared by the hydrothermal method, as shown in Table 2.
[0042] Table 2 Catalytic effects of ZnIn2S4 catalysts prepared by different preparation methods
[0043] The contents described in this specification are merely an enumeration of implementation forms of the inventive concept, and the protection scope of the present invention should not be regarded as being limited to the specific forms described in the embodiments.
Claims
1. A method for synthesizing spinel nanomaterials based on subcritical technology, characterized in that: The following steps are involved: 1) Dissolve a variety of metal salts in ultrapure water, perform ultrasonic homogenization and set aside, weigh an organic additive and dissolve it in ultrapure water, mix the solutions to obtain a mixed solution, and transfer it to a subcritical high-pressure reactor after ultrasonication; 2) dispersing the alkaline additive in ultrapure water to obtain an alkaline solution, and dropping the alkaline solution into the mixed solution obtained in step 1), stirring and mixing evenly, sealing the reactor, and introducing gas; under magnetic stirring, precisely controlling the temperature and pressure in the subcritical high-pressure reactor by a heating and pressurizing device, and maintaining the temperature and pressure for 30 to 180 minutes, so as to form a subcritical fluid in the subcritical high-pressure reactor; 3) After the reaction is completed, the solution prepared in step 2) is centrifuged, washed with ultrapure water and anhydrous ethanol to remove residual salt, and dried in an oven overnight to obtain a spinel nano-micro material.
2. The method for synthesizing spinel nanomaterials based on subcritical technology according to claim 1, characterized in that: In step 1), the metal salt is a nitrate or chloride of aluminum, cobalt, manganese, zinc, bismuth, indium or iron.
3. The method for synthesizing spinel nanomaterials based on subcritical technology according to claim 1, characterized in that: In step 1), the organic additive is citric acid, thioacetamide, cetyltrimethylammonium bromide or urea, and the molar ratio of the total metal atoms in the metal salt solution to the amount of the organic additive added is 1:0.8-5.
4. The method for synthesizing spinel nanomaterials based on subcritical technology according to claim 1, characterized in that: In step 2), the alkaline additive is sodium hydroxide, ammonia water, carbonate or bicarbonate, and the molar ratio of the amount of the alkaline additive in the alkaline solution to the total metal atoms in the metal salt solution is 2-8:
1.
5. The method for synthesizing spinel nanomaterials based on subcritical technology according to claim 1, characterized in that: In step 2), the temperature is controlled at 160-180°C. When the prepared spinel nanomaterial is a sulfide catalyst, nitrogen is used. When the prepared spinel nanomaterial is an oxidation catalyst, oxygen is used.
Citation Information
Patent Citations
Preparation method of lithium-metal composite oxides
CN101443273A
Preparation method of three-dimensional flower-shaped nickel cobaltate nano-sheet mesoporous microspheres
CN104773764A
Nano lanthanum cobaltate material and preparation method thereof
CN108144623A
Preparation method of sea-urchin-shaped cobalt acid copper nanometer material of nickel foam load
CN108346521A
Preparation method and applications of carbon nano-tube-supported transition metal oxide material
CN108682868A